Construction and evaluation of online course on prevention of hypertension for blind people - Luciana Vieira de Carvalho (2015)
Due to altered visual function, blind people are more exposed to risk factors of hypertension, a situation that proves the need to promote educational actions to prevent this disease. The objective was to develop affordable online course for the blind ones on prevention of hypertension. It was used Development Model of Digital Educational Material composed by five phases entitled Analysis and Planning; modeling; implementation; Evaluation and Maintenance; Distribution. In Analysis and Planning phase the product was characterized. The course about hypertension in online mode was directed to blind population. It was built in modeling a script and it was added a content to multimedia elements, being transformed into the pages for internet format with definition of navigation tools and design. There was obtained 15 pages that were divided into six educational modules. The study followed the accessibility standards of national documents (e-MAG) and international (WCAG). In the Deployment it was submit the accessibility evaluating course pages. Initially we used the software ASES that generated Error Reporting, accusing infringement of four national recommendations and three international principles. The pages were reviewed, and the inconsistencies were corrected. In the second test, the pages were lodged into SOLAR environment. It was contacted four blind people whom rated platform accessibility and usability of the platform by performing sequential activities of navigation. It was found that the SOLAR is partially accessible as it found some accessibility barriers (lack of field identification, disposal and inadequate identification fields and links; elements that prevented reading the content in a logical sequence and using the mouse). Therefore, the SOLAR needs improvement to facilitate navigation by the blind. The course components such as texts; images; audio and links were considered accessible, and the initial difficulty in navigation was, to be hosted, on the platform that needed improvements. The Evaluation and Maintenance occurred throughout the course preparation and the distribution will be addressed in further studies. The course did not suffer any changes and the prototype implemented in SOLAR was taken as the result of the research. It concludes that build online course as assistive technology for the blind is a viable task. This study provides information about prevention of hypertension and equal access to digital educational materials. The study encourages nurses to develop affordable technologies for health promotion of blind people.